Pengembangan Media Gambar Yang Efektif Pada Materi Aku Ciptaan Tuhan Dalam Pembelajaran Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas I Sekolah Dasar - Putri Damero Sitorus; Lustani Samosir; Hasudungan Simatupang; Wlson Simanjuntak; Elvri T. Simbolon (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to produce image media which is based on the expectations of PAK teachers regarding the importance of image media in the material I am God's Creation in learning PAK and Characteristics for grade 1 elementary school. The research uses a development approach (research and development) which aims to produce image media products that are effective for use in Christian Religious Education learning with the material I am God's Creation for grade I elementary school. The research location is a State Elementary School in Sipoholon District, North Tapanuli Regency. The research was carried out from August to September 2023. Development steps using the ADDIE model. From the research results it is known: 1) Analysis, results of questionnaire answers by ten teachers that 88.33% require the development of image media that makes it easier for teachers to teach and attract students' attention to learning material I am God's creation. 2) Design, a) Making drawings of body parts and body function. b) Determination of learning materials. I am God's creation from the book of Genesis 1:27. c) Reviewing material in images according to the 2013 curriculum. 3) Development of a validator for media validation in image media has been improved and is suitable for use in field trials. 4) Implementation, the result is that 78% of grade I elementary school teachers in Sipoholon District strongly agree that the content of the material and the quality of the media in the material images I am God's Creation are good and can be used effectively in learning. 5) Evaluation, spiritual assessment of students is known to have achieved 97.97%, social assessment of students is known to have achieved 97.12%, cognitive and spicomotor assessments can be known directly from students' answers and abilities to questions given by the Christian Religious Education teacher after being taught the material I am a creation God uses image media and has shown results in the very good category, which means that through learning using image media, students are able to be grateful for God's creation within themselves and will try to use their body parts to carry out good activities and glorify God in their daily lives.